Histologically proven AMA positive primary biliary cholangitis but normal serum alkaline phosphatase: Is alkaline phosphatase truly a surrogate marker?. (May 2019) - Sun, Chunyan; Xiao, Xiao; Yan, Li; Sheng, Li; Wang, Qixia; Jiang, Pan; Lian, Min; Li, Yanmei; Wei, Yiran; Zhang, Jun; Chen, Yong; Li, Bo; et al.
Abstract: Background and aims: The most highly directed and specific autoantibody in human immunopathology is the serologic hallmark of primary biliary cholangitis (PBC), antimitochondrial antibodies (AMAs). However the clinical significance of finding a positive AMA, with normal alkaline phosphatase (ALP) remains enigmatic. Methods: We took advantage of 169 consecutive outpatients who were identified as having a positive AMA, but normal ALP levels between January 2012 and January 2018. A liver biopsy wasperformed on 67/169 of these AMA positive normal ALP patients. Results: In all 169 patients we reconfirmed the AMA and also performed anti-gp210 and anti-sp100, liver stiffness (LSM) assessed by vibration-controlled transient elastography (VCTE), an abdominal computed tomography (CT) scan, and either a magnetic resonance imaging (MRI) or ultrasound. The liver biopsies were reviewed by two unbiased observers. 87.6% of the 169 patients were females with a mean age of 46; the median AMA titer 1:320; an elevated serum IgM was found in 53.3%. Importantly, in patients with a liver biopsy, 55（82.1%）out of 67 had varying degrees of cholangitis activity, diagnostic of PBC. Conclusion: In patients who were AMA-positive but had normal ALP levels, more than 80% were associated with histological classic PBC. These data emphasize the importance of a positive AMA, even with a normal ALP and also question the role of ALP as a sole surrogate marker of cholangitis. Highlights: We researched the histological features of the patients with AMA-positive results and normal ALP levels. For the AMA positive patient with normal ALP, timely liver biopsy was essential, especially when ALP > 0.475 ULN and AMA ≥ 1:320. Our data question the reliability of relying on ALP as the solo biochemical surrogate marker of cholangitis.